A Study on the Eigenmodes Constructed in the Conductor Backed Coplanar Waveguide - Kim, Yeong Min (Transactions on Engineering and Computing Sciences, 2023)
Finite element method (FEM) is applied to obtain eigenmodes constructed in the conductor backed coplanar waveguide. The eigenmodes for coplanar and microstrip waveguides are also calculated for understanding the eigen properties of this waveguide. The cross sections of the waveguides are divided into the simple triangular elements in the calculations. The edge vectors and nodes of an element are basic components for constructing the eigenmodes of the waveguides. The vector Helmholtz equation is made to the eigen matrices in the process of FEM. Those eigen matrices are diagonalized by the Krylov-Schur iteration method. The eigenmodes are obtained from the similar transform matrices diagonalizing the eigen matrices. As results, specific eigen spectra representing the properties of the waveguides have been revealed schematically and compared with each other.